Environmental Impact Assessment of Vehicular Traffic along Major Roads in Delta State of Nigeria, Using Contamination and Enrichment Factors - H. O. Juwah; O. Z. Tachere (Archives of Current Research International, 2021)
This research was carried out to evaluate the impact of vehicular traffic, on the soil and grasses growing along major roadsides in Delta state, Nigeria. Soil and Guinea grass samples were collected from three major roads, and a control point in Delta State. The collected samples (plant and soil) were digested according to standard procedures, and their heavy metals (Fe, Cu, Pb and Ni) concentrations were analyzed by using the Atomic Absorption Spectrophotometry. Results obtained indicated that the soil and grass heavy metals concentrations were significantly (p ≤0.05) higher than the control point, and varied across the sampled locations. It was observed from the resulted that, there was heavy metals accumulation in the soil and plants growing along the roadsides. Irrespective of the sampling location, the concentrations of the heavy metals followed this trend Fe ˃Pb ˃Ni ˃ Cu. As revealed by the results, at Ughelli, the contamination factor was in this order Ni > Cu >Fe >Pb; then at Ozoro road, the contamination factor ranking was Ni >Pb >Fe Cu; while at Irri road, the contamination ranked Ni > Cu > Pb > Fe. This showed that Ni had the highest contamination factor, regardless of the road location. As portrayed by the results, the heavy metals enrichment factors were greater than 1. The results revealed that the heavy metals enrichment factors followed this ranking Ni > Cu > Pb in all the locations sampled. These results indicated that the roadsides soil and Guinea grass received their pollution from anthropogenic sources, and vehicular emissions in particular. The results obtained from this study revealed the urgency of the government to decongest vehicular traffic, to prevent accumulation of toxic heavy metals in the ecosystems.